1978
DOI: 10.1007/bf00931717
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the free-living phase of the cat hookworm life cycle

Abstract: Laboratory studies were undertaken to evaluate the role of environmental factors on the development of free-living stages of the cat hookworm Ancylostoma tubaeforme. An index of development calculated from the proportion of eggs that developed to the infective stage and the reciprocal of the development period, has suggested that the absence of 'high' temperatures (26 degrees - 30 degrees C) would significantly affect the L3 population in contaminated soils. There were, however, no significant differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Relationship between temperature (a) parasite survival and (b) development duration. Points indicate experimental data (Seamster, 1950; Beer, 1973; Nwosu, 1978; Udonsi & Atata, 1987) and lines are fits derived from fractional polynomials analyses. Regression details: parasite survival y = 0.884 + −22.88 x −0.5 + −7.73ln( x ); A. lumbricoides duration y = 8.601 + −63.718 x − −2 + 2.526 x −3 ; T. trichiura duration y = 26.079 + 41209.68 x −−2 + −1715.02 x —2 ; hookworm duration y = 3.701 + 40.88 x −−2 + −46.18 x −−2 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Relationship between temperature (a) parasite survival and (b) development duration. Points indicate experimental data (Seamster, 1950; Beer, 1973; Nwosu, 1978; Udonsi & Atata, 1987) and lines are fits derived from fractional polynomials analyses. Regression details: parasite survival y = 0.884 + −22.88 x −0.5 + −7.73ln( x ); A. lumbricoides duration y = 8.601 + −63.718 x − −2 + 2.526 x −3 ; T. trichiura duration y = 26.079 + 41209.68 x −−2 + −1715.02 x —2 ; hookworm duration y = 3.701 + 40.88 x −−2 + −46.18 x −−2 …”
Section: Figurementioning
confidence: 99%
“… † Data taken from Anderson (1982); Bundy & Cooper (1989); Crompton (2001) ‡ Data taken from Anderson & May (1991) § Data on A. lumbricoides (Seamster (1950); T. suis (Beer, 1976); hookworm (Nwosu, 1978; Smith & Schad, 1989). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Chandler concluded that 20-30 °C was optimal for transmission with larvae reaching maturity in five days, with the lower limit lying between 8-10 °C and the upper limit 40-45 °C. Available experimental data indicate that above temperatures of 35-40 °C development of eggs arrests and death occurs (Nwosu, 1978; Udonsi and Atata, 1987; Smith and Schad, 1990). For example, Udonsi and Atata (1987) showed that at temperatures of 35 °C larvae of Necator americanus were all dead, with the highest cumulative hatching rates obtained at 30 °C.…”
Section: Epidemiology and Transmission Dynamicsmentioning
confidence: 99%
“…(CLARKE & PERRY, 1977) has been studied as the first stage in the infection process, rather less attention has been paid to the eggs of those nematodes that hatch spontaneously. Much of the work that has been done has concentrated on over-all development times from egg release in the faeces to development of infective third-stage larvae (BELLE, 1959;GIBBS & GIBBS, 1959;PRASAD, 1959;SILVERMAN & CAMPBELL, 1959;PANDEY, 1972, Nwosu, 1978. However, WILSON (1958) using Trichostrongylus retortaeformis, CROLL (1974) with Necator americanus and VINA YAK et al (1978) with Ancylostoma duodenale looked directly at egg development and emergence of the first-stage larvae.…”
Section: Introductionmentioning
confidence: 99%